My Post Graduate and Professional Research and Study on Chartered Management - Iqbal Shaukat (Indonesian Journal of Education and Science, 2026)
Chartered management qualification is very important in this age ofmanage globalization.In chartered manager we study the different stream of management.In chartered manager we study about the buying and selling material,we study about the economic order quantity of material management.In the chartered manager we study all the aspects of material management, which is relate to production and operation management.In the chartered manager we study about the operation management with detail and study case.in the chartered manager we can learn about the utilization of resource under the principles of operation management,in operation management we study about the best location of resources and it utilization according to the needs.In the Chartered Management, we study quality control and project management.